2019
DOI: 10.1142/s021773231950086x
|View full text |Cite
|
Sign up to set email alerts
|

Tsallis agegraphic dark energy model

Abstract: Not affiliated with any institution, Kazerun, Iran.The cosmological implications of interacting and non-interacting new Tsallis agegraphic dark energy with cold dark matter in the framework of flat Fractal cosmology is discussed. The physical significant of statefinder diagnostics and ωD − ω ′ D plane in both interacting and non-interacting scenarios are also invetigated. The study shows that the equation of state (EoS) parameter corresponds to the quintessence region in both interacting and non-interacting sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…In the studies, we found that the FRW equations can be also regarded as the first law of thermodynamics when we consider the Bekenstein-Hawking entropy by using the cosmological apparent horizon [83][84][85] as a realization of the thermodynamics of space-time [80]. If, however, there are long range forces, such as the electromagnetic force and the gravitational force, we know that the systems are non-additive systems and the standard Boltzmann-Gibbs additive entropy should not be applied and we should generalize the entropy to the non-extensive Tsallis entropy [49][50][51], and recently there were several attempts in this regard (see [52][53][54][55][56][57][58][59][60][61][62]). If we apply Tsallis entropy to the black hole, instead of Bekenstein-Hawking entropy, one finds [52],…”
Section: The Thermodynamics Of Space-time and Applications To Cosmologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies, we found that the FRW equations can be also regarded as the first law of thermodynamics when we consider the Bekenstein-Hawking entropy by using the cosmological apparent horizon [83][84][85] as a realization of the thermodynamics of space-time [80]. If, however, there are long range forces, such as the electromagnetic force and the gravitational force, we know that the systems are non-additive systems and the standard Boltzmann-Gibbs additive entropy should not be applied and we should generalize the entropy to the non-extensive Tsallis entropy [49][50][51], and recently there were several attempts in this regard (see [52][53][54][55][56][57][58][59][60][61][62]). If we apply Tsallis entropy to the black hole, instead of Bekenstein-Hawking entropy, one finds [52],…”
Section: The Thermodynamics Of Space-time and Applications To Cosmologymentioning
confidence: 99%
“…In the present paper, we intend to address the above questions. For this purpose, we consider several entropic DE models, such as the Tsallis entropic DE [49][50][51][52][53][54][55][56][57][58][59][60][61][62], the Rényi entropic DE [63][64][65][66][67][68], and the Sharma-Mittal entropic DE [67,69,70]. Here it may be mentioned that unlike the Tsallis and Rényi entropy functions, Sharma-Mittal entropy represents a more general two-parameter function.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a new HDE model has been proposed by using the holographic hypothesis and the Tsallis entropy [33], named Tsallis holographic dark energy (THDE) [34,35]. As a result, recently, several THDE models have been investigated and explored in different scenarios with an aim to search for the dynamics of the universe and one can look into [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] for a comprehensive review.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, four new holographic dark energy models (HDE) [33][34][35][36] have been introduced to associate multiple generalized entropies of the FRW Universe horizon. In the present work, the focus is on the Tsallis holographic dark energy [33] inspired by the Tsallis entropy [30].…”
Section: Introductionmentioning
confidence: 99%
“…The point that practicing system horizon in the Tsallis statistics, we can achieve the Bekenstein entropy, which is the determination of all these efforts [37,38]. The authors also exposed adequate stability by the concerned models [33][34][35][36]. To examine the cosmological and gravitational systems of the generalized statistical mechanics [39][40][41][42][43][44][45][46] framework, positively a crucial role is performed by Tsallis definition of entropy [30].…”
Section: Introductionmentioning
confidence: 99%